Genomic evidence of gene flow during reinforcement in Texas Phlox. Issue 8 (6th March 2017) - Roda, Federico; Mendes, Fábio K.; Hahn, Matthew W.; Hopkins, Robin
Abstract: Gene flow can impede the evolution of reproductive isolating barriers between species. Reinforcement is the process by which prezygotic reproductive isolation evolves in sympatry due to selection to decrease costly hybridization. It is known that reinforcement can be prevented by too much gene flow, but we still do not know how often have prezygotic barriers evolved in the presence of gene flow or how much gene flow can occur during reinforcement. Flower colour divergence in the native Texas wildflower, Phlox drummondii, is one of the best‐studied cases of reinforcement. Here we use genomic analyses to infer gene flow between P. drummondii and a closely related sympatric species, Phlox cuspidata . We de novo assemble transcriptomes of four Phlox species to determine the phylogenetic relationships between these species and find extensive discordance among gene tree topologies across genes. We find evidence of introgression between sympatric P. drummondii and P. cuspidata using the D‐ statistic, and use phylogenetic analyses to infer the predominant direction of introgression. We investigate geographic variation in gene flow by comparing the relative divergence of genes displaying discordant gene trees between an allopatric and sympatric sample. These analyses support the hypothesis that sympatric P. drummondii has experienced gene flow with P. cuspidata . We find that gene flow between these species is asymmetrical, which could explain why reinforcement caused divergence in only one of the sympatric species. Given the previous research in this system, we suggest strong selection can explain how reinforcement successfully evolved in this system despite gene flow in sympatry.